We have the formula a+(n-1)d=nth term
Where a is the 1st term ,d is the difference and n is the nth term
So1st term= a
2nd term= (a+1)d
3rd term= (a+2)d
Adding ad+2d+ad+ 4d= 38
2ad+ 6d= 38
In the same way 7th term=(a+6)d
Adding these 2ad+15d=83
Subtracting, 9d= 45 which makes d=5
a+2d + a+4d=38 -->2a + 6d = 38
a+6d + a+9d = 83 --> 2a + 15d = 83
9d = 45
back in 2a+6d = 38
the sequence is:
4 9 14 19 24 ...
BTW, the definitions used by Praphul are not correct.
e.g. he said:
5th term is (a+4)d
that should have been a + 4d, the brackets there are critical
Maths - The 5th term of an exponential sequence is 4 and of 2nd term is 35(¡)...
maths - the 3rd term of a g.p is 63 while the 5th term is 567,what is the sum of...
Math 12 - sum of 2nd and 5th terms of a geometric sequence is 13. the sum of ...
maths - the sum of the 4th and 6th terms of an A.P is 42. the sum of the 3rd and...
world issuse - I'm a 7 letter word u read daily,my 5th 6th and 7th letter ...
pre-algebra - find the product: (4k to the 5th power)(-2k)to the 3rd power. 5th ...
maths - can you replace the stars with figures **** x 3 ______ ***** the whole ...
arithmetic - THE SUM OF THE 2ND AND 5TH TERMS OF AN A.P IS 42. IF THE DIFFERENCE...
Maths - Find three no. Such that,the 2nd is twice the 1st,the 3rd is three times...
maths - in an A.p 6th term is half the 4th term and the 3rd term is 15.How many ...